2019
DOI: 10.1590/1807-1929/agriambi.v23n11p847-851
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of densely cultivated onion cultivars as function of nitrogen fertilization

Abstract: Nitrogen exerts a marked influence on the yield and quality of the onion. The present work was developed from June to October 2016, aiming to evaluate the yield and quality of two cultivars of onion under a system densified as a function of nitrogen doses in Mossoró, RN, Brazil. A randomized block design was used in a 2 x 7 factorial scheme, with four repetitions, corresponding to two cultivars (IPA 11 and Rio das Antas) and seven nitrogen doses (0, 45, 90, 135, 180, 225 and 270 kg ha-1 of N), provided by fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
(12 reference statements)
1
7
0
1
Order By: Relevance
“…The yield registered in the current experiment is near the productivity observed in other studies carried out within and abroad of Europe [66][67][68]. In particular, concerning fertilization management, as in our experiment, the highest yield with similar production was also obtained with a dose of 180 kg N ha −1 by Díaz-Pérez et al [69], Rodrigues et al [70], and Gonçalves et al [71]. Onion yield is strictly linked to N fertilization and is directly proportional to the amount of N supplied to the crop.…”
Section: Ec [µS CMsupporting
confidence: 83%
“…The yield registered in the current experiment is near the productivity observed in other studies carried out within and abroad of Europe [66][67][68]. In particular, concerning fertilization management, as in our experiment, the highest yield with similar production was also obtained with a dose of 180 kg N ha −1 by Díaz-Pérez et al [69], Rodrigues et al [70], and Gonçalves et al [71]. Onion yield is strictly linked to N fertilization and is directly proportional to the amount of N supplied to the crop.…”
Section: Ec [µS CMsupporting
confidence: 83%
“…As can be seen from the pairs of onions (one treated with urea and one treated with SAN) in the pictures in Figure 8, the SAN treatment resulted in increased size and harvestable yield while the amount of nitrogen applied was only 2.7 kg N ha −1 in the SAN treatment compared to the UK industry standard of 150 kg N ha −1 [3]. Previous work found that the optimum rate of nitrogen application for onions was between 92 and 263 kg N ha −1 [7][8][9][10]22], while with targeted applications during the growing season a rate of 20 kg N ha −1 [3] was shown to be suitable for achieving good yields. This work showed that it is possible to use even lower nitrogen rates of 2.7 kg N ha −1 .…”
Section: Discussionmentioning
confidence: 92%
“…Published work on onion nutrition used a range of nitrogen application rates, for example, 100 and 200 kg N ha −1 [6], 0-270 kg N ha −1 [7], 210-315 kg N ha −1 [8] and 102-302 kg N ha −1 [9], and the optimal rates for production were 92 kg N ha −1 [7], 263 kg N ha −1 [8], 162 kg N ha −1 [9] and 134 kg N −1 ha [10]. Additionally, the form of the nitrogen (urea, ammonium nitrate or calcium nitrate) was shown to not influence yield [6].…”
Section: Introductionmentioning
confidence: 99%
“…Argissolo e Neossolo, respectivamente (Figura 1D). Aumento da produtividade de bulbos de classes com maior diâmetro com o incremento de doses de N e a redução na produtividade de bulbos de menor diâmetro tem sido observado (CECÍLIO FILHO et al, 2010;KURTZ et al, 2012;COSTA, 2014aCOSTA, e 2014bRODRIGUES et al, 2015;MENEZES JÚNIOR;KURTZ, 2016;GONÇALVES et al, 2019).…”
Section: Methodsunclassified